2007
DOI: 10.1111/j.1460-9592.2007.02378.x
|View full text |Cite
|
Sign up to set email alerts
|

Early awakening and extubation with remifentanil in ventilated premature neonates

Abstract: Our results show an interesting potential for the use of remifentanil in premature neonates. Remifentanil allowed an adequate level of sedation and analgesia as well as rapid recovery after discontinuation. However, further properly designed clinical trials are needed before it can be generally recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…Unfortunately, many premedication regimens are not well evaluated in prospective trials in the neonate, and hence the most appropriate selection and indeed the safety of some of these medications in this population remain unclear. This double-blind randomised controlled trial adds to a growing body of evidence on the use of remifentanil in neonates and very low birthweight infants, which, to date, has been very limited 10 1315 20 21. While our results demonstrate that remifentanil combined with atropine maintained haemodynamic and oxygenation parameters comparable to the traditional regimen of fentanyl, succinylcholine and atropine, the intubation conditions reported by intubators were felt to be less optimal with remifentanil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, many premedication regimens are not well evaluated in prospective trials in the neonate, and hence the most appropriate selection and indeed the safety of some of these medications in this population remain unclear. This double-blind randomised controlled trial adds to a growing body of evidence on the use of remifentanil in neonates and very low birthweight infants, which, to date, has been very limited 10 1315 20 21. While our results demonstrate that remifentanil combined with atropine maintained haemodynamic and oxygenation parameters comparable to the traditional regimen of fentanyl, succinylcholine and atropine, the intubation conditions reported by intubators were felt to be less optimal with remifentanil.…”
Section: Discussionmentioning
confidence: 99%
“…Remifentanil has a rapid onset of action (60–90 s) and at adequate doses renders the patient apnoeic and motionless, thus reducing the need for a muscle relaxant 12. The experience with remifentanil in the neonatal literature to date is extremely limited; however, earlier reports suggest that remifentanil may provide adequate sedation, analgesia and intubation conditions in this population 1315. The objective of this trial was to evaluate the safety and efficacy of remifentanil in term and preterm neonates undergoing non-urgent endotracheal intubation.…”
mentioning
confidence: 99%
“…Besides, several studies have demonstrated the safety and efficacy of remifentanil in analgesia and anesthesia of newborns, at term and premature 32,33,58 . Since remifentanil does not have residual sedation after it is discontinued, it became an option for sedation and analgesia of premature neonates 59,60 .…”
Section: Resultsmentioning
confidence: 99%
“…Assim, vários estudos têm mostrado a segurança e eficá-cia do remifentanil na analgesia e anestesia de crianças e recém-nascidos, assim como em recém-nascidos prematuros 32,33,58 . Como o remifentanil não apresenta efeito de sedação residual após sua suspensão, pode-se tornar uma opção na sedação e analgesia de recém-nascidos prematuros 59,60 .…”
Section: Conclusãounclassified
“…It appears that the advantage of a short elimination in comparison with longer acting opioids also holds true with preterm babies. After termination of infusions of morphine or remifentanil in intensive care for respiratory distress syndrome, the length of time required to awaken and extubate the neonates was 18.9-and 12.1-fold longer, respectively, in the morphine group than in the remifentanil group (Silva et al 2008). The first of the four RCTs comparing remifentanil and pethidine in labour analgesia was interrupted due to the lower Apgar scores in the pethidine group in an interim analysis of the data (Volikas and Male 2001).…”
Section: Effects Of Maternal Analgesia On the Neonatementioning
confidence: 99%